2001
DOI: 10.1074/jbc.m009562200
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Membrane Type 1-Matrix Metalloproteinase

Abstract: Membrane type 1-matrix metalloproteinase (MT1-MMP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…11,33) Shankavaram et al also demonstrated that induction of monocyte MT1-MMP is regulated through the PG E 2 /cAMP pathway, indicating the important role of COX-2 in the regulation of MT1-MMP. 14) Taken together, these facts imply that MT1-MMP production through the COX-2 dependent pathway may also promote plaque instability, as does the production of other MMPs, including MMP-2 and MMP-9. 12,20) In our WHHLMI rabbits, relatively strong COX-2 staining was found also in more stable atherosclerotic lesions, such as neointimal and collagen-rich lesions (Figs.…”
Section: Distribution Of Cox-2 In Relation To Mt1-mmp Distributionmentioning
confidence: 95%
See 3 more Smart Citations
“…11,33) Shankavaram et al also demonstrated that induction of monocyte MT1-MMP is regulated through the PG E 2 /cAMP pathway, indicating the important role of COX-2 in the regulation of MT1-MMP. 14) Taken together, these facts imply that MT1-MMP production through the COX-2 dependent pathway may also promote plaque instability, as does the production of other MMPs, including MMP-2 and MMP-9. 12,20) In our WHHLMI rabbits, relatively strong COX-2 staining was found also in more stable atherosclerotic lesions, such as neointimal and collagen-rich lesions (Figs.…”
Section: Distribution Of Cox-2 In Relation To Mt1-mmp Distributionmentioning
confidence: 95%
“…4,31) On the other hand, it is reported that MT1-MMP provided by macrophages may play a significant role in the activation of MMP-2 produced by other cells, such as SMCs. 11,14) MMP-2 is constitutively expressed in medial SMCs. 31) These facts may be another explanation for the uncoupling of MT1-MMP and MMP-2 distribution in the medial regions (SMCs).…”
Section: Distribution Of Mt1-mmp/mmp-2mentioning
confidence: 99%
See 2 more Smart Citations
“…2,11 Oxidative stress can damage laminar epidermal cells because these cells have a lower metabolic rate than do epithelial cells in other organs, and the relative lack of superoxide dismutase activity makes them ill-equipped to deal with excessive amounts of ROS. 5,9 Furthermore, ROS induce cyclooxygenase-2 expression, 50 and a cyclooxygenase-2 metabolite, prostaglandin E 2 , has been found to promote the release and activation of matrix metalloproteinases-2 and -9 51 ; those matrix metalloproteinases are thought to play an important role in degradation of the basement membrane during acute laminitis. 46,52,53 Additionally, the myeloperoxidase-hydrogen peroxide system is able to inactivate antiprotease activity, 54 which creates an environment that favors the activity of proteases such as matrix metalloproteinases; this may contribute to additional laminar tissue damage.…”
Section: Discussionmentioning
confidence: 99%